Modulation of PI3K/Akt/GSK3β signaling cascade through G protein-coupled receptor 55 (GPR55) activation: Prenatal lysophosphatidylinositol attenuates valproic acid-induced synaptic abnormalities and mitochondrial dysfunction - Ahmed, Shamim; Abir, Ariful Haque; Sharmin, Ozayra; Khurshid, Neda; Akter, Amana; Nakshy, Nafisa Tajneen; Hasan, Md Mahmudul; Yesmine, Saquiba; Rahman, Mahbubur (Life Sciences, 2023)
Aims: Dysregulation of PI3K/Akt/GSK3β signaling has been implicated in various neurological disorders, including autism spectrum disorder (ASD). G protein-coupled receptor 55 (GPR55) has recently emerged as a potential regulator of this signaling cascade. This study explores the intricate modulation of the PI3K/Akt/GSK3β signaling cascade via GPR55 activation and its potential therapeutic implications in the context of autism-associated neuronal impairments. Main methods: Valproic acid (VPA) was administered on embryonic day 12 (E12) to induce ASD, and lysophosphatidylinositol (LPI), a GPR55 agonist, was used prenatally to modulate the receptor activity. Golgi-cox staining was performed to observe neuronal morphology, and Hematoxylin and eosin (H and E) staining was carried out to quantify damaged neurons. Enzyme-linked immunosorbent assay (ELISA) was implemented to identify molecular mediators involved in neuroprotection. Key findings: Prenatal VPA exposure resulted in significant abnormalities in synaptic development, which were further evidenced by impairments in social interaction and cognitive function. When LPI was administered, most of the synaptic abnormalities were alleviated, as reflected by higher neuron and dendritic spine count. LPI treatment also reduced cytoplasmic cytochrome c concentration and related neuronal cell death. Mechanistically, GPR55 activation by LPI increases the expression of phospho-Akt and phospho-GSK3β, leading to the activation of this signaling in the process of rescuing synaptic abnormalities and mitochondria-mediated neuronal apoptosis. Significance: The observed therapeutic effects of GPR55 activation shed light on its significance as a prospective target for ameliorating mitochondrial dysfunction and dendritic spine loss, offering novel prospects for developing targeted interventions to alleviate the neuropathological causes of ASD.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Dendritic spine; GPR55; GSK3β; Lysophosphatidylinositol (LPI); Mitochondrial dysfunction; Neuronal apoptosis